Witnessing others interact with a novel object has sex- and size-specific effects on neophilia in mosquitofish - Barbosa, Angela J.; McGhee, Katie E. (Behavioural processes, 2026)
Dealing with novelty can be challenging for animals. Approaching unfamiliar objects and environments allows individuals to discover and exploit new food sources and habitats, but novelty can also be dangerous and expose individuals to unfamiliar predators or toxic foods. Observing how others react to novel objects can enable an individual to indirectly assess the risks or benefits associated with particular objects without putting themselves directly in harm’s way via social transmission of information. Using the western mosquitofish (Gambusia affinis), we first manipulated whether individuals either witnessed a group of conspecifics interacting with a novel object in a beaker (shoal treatment) or witnessed the novel object alone in an empty beaker (alone treatment). Following this exposure, individuals then encountered that same object on their own and we measured how quickly they approached the object. We found that the effect of witnessing a group encounter a novel object depended on the sex and size of the focal individual. Seeing a group around a novel object caused males and similarly small-sized females to approach the object more quickly when they encountered it on their own later, compared to seeing the novel object without surrounding conspecifics. In contrast, large females were willing to approach the object regardless of the social context under which they had first encountered it. Sex, body size, and/or personality differences might affect the benefits of the social context and determine whether conspecifics attract individuals to a novel object. •Being in a group allows social transmission of information about novel objects.•Witnessing an object with others might affect perception of that object later on.•Males approached the object faster when they had encountered it first with a group.•Small females behaved similarly to males but large females did not.•Sex, size, and personality could shape how social context affects novelty.